Antecedents of stock market performance in Malaysia from macroeconomics perspectives / Noor Azida Noor Azizi - Noor Azizi, Noor Azida (Faculty of Business and Management, 2018)
The main of objective of this study to investigate the relationship between macroeconomic variables which consist of Exchange Rate, Money Supply and Gross Domestic Product towards the stock market in Malaysia that represent by FTSE Bursa Malaysia KLCI index. The study employed Multiple Linear Regression in order to find the relationships among independent variables and dependent variable. The data is collected from year 1987 until 2017 and it is conduct in yearly basis which is 30 years observations. From the result, it reveals that Money Supply has a positive insignificant relationship towards stock market (FTSE Bursa Malaysia KLCI). While Gross Domestic Product found significantly positive relationship towards stock market performance in Malaysia and Exchange Rate found significantly negative relationship between stock market performances in Malaysia. These results give additional understanding of the relationship between the macroeconomic variables and FTSE Bursa Malaysia KLCI plus it might also to be helpful for the speculator, regulator and investor.